PENGARUH LUAS LAHAN, TENAGA KERJA DAN PUPUK TERHADAP HASIL PRODUKSI KARET DI DESA SUNGAI BOKOR KECAMATAN MATARAMAN KABUPATEN BANJAR - NOVI APRIYANTI (PPJP Universitas Lambung Mangkurat, 2018)
Each rubber farmer has different results. The difference is influenced by several factors. In the production procces the output is strongly influenced by this inputs, in which the context between output and input is describes in the production function. The purpose of this research is to see the effect of land area, labor and fertilizer on rubber production.The research uses primary and secondary data which is quantitative research. Sampling amounted to 64 farmers. Data collection techniques using questionnaire, in depth interview and observation. Analysis technique using Cobb-Douglas function that has been transformed into natural logarithma that is using multiple regression.And the result of this study is the land area(X1), labor(X2) and fertilizer(X3). Simultaneously affect the production of rubber(Y). But partially only the area of land affecting the production of rubber. In this study the significant and most dominant production factors affect the rubber production in the village of Sungai Bokor, Mataraman, Banjar Is Land Area.Keywords : production(Y), land area(X1), labor (X2) and fertilizer(X3).